LO86: Lack of association between four biomarkers and the presence of persistent post-concussion symptoms after a mild traumatic brain injury. (May 2020) - Le Sage, N.; Le Sage, N.; Frenette, J.; Chauny, J.; Berthelot, S.; Archambault, P.; Perry, J.; Lee, J.; Lang, E.; McRae, A.; Neveu, X.; Tardif, P.; et al.
Abstract : Introduction: Mild Traumatic Brain Injury (mTBI) is a common problem: each year in Canada, its incidence is estimated at 500-600 cases per 100 000. Between 10 and 56% of mTBI patients develop persistent post-concussion symptoms (PPCS) that can last for more than 90 days. It is therefore important for clinicians to identify patients who are at risk of developing PPCS. We hypothesized that blood biomarkers drawn upon patient arrival to the Emergency Department (ED) could help predict PPCS. The main objective of this project was to measure the association between four biomarkers and the incidence of PPCS 90 days post mTBI. Methods: Patients were recruited in seven Canadian ED. Non-hospitalized patients, aged ≥14 years old with a documented mTBI that occurred ≤24 hrs of ED consultation, with a GCS ≥13 at arrival were included. Sociodemographic and clinical data as well as blood samples were collected in the ED. A standardized telephone questionnaire was administered at 90 days post ED visit. The following biomarkers were analyzed using enzyme-linked immunosorbent assay (ELISA): S100B protein, Neuron Specific Enolase (NSE), cleaved-Tau (c-Tau) and Glial fibrillary acidic protein (GFAP). The primary outcome measure was the presence of persistent symptoms at 90 days after mTBI, as assessed using the Rivermead Post-Concussion symptoms Questionnaire (RPQ). A ROC curve was constructed for each biomarker. Results: 1276 patients were included in the study. The median age for this cohort was 39 (IQR 23-57) years old, 61% were male and 15% suffered PPCS. The median values (IQR) for patients with PPCS compared to those without were: 43 pg/mL (26-67) versus 42 pg/mL (24-70) for S100B protein, 50 pg/mL (50-223) versus 50 pg/mL (50-199) for NSE, 2929 pg/mL (1733-4744) versus 3180 pg/mL (1835-4761) for c-Tau and 1644 pg/mL (650-3215) versus 1894 pg/mL (700-3498) for GFAP. For each of these biomarkers, Areas Under the Curve (AUC) were 0.495, 0.495, 0.51 and 0.54, respectively. Conclusion: Among mTBI patients, S100B protein, NSE, c-Tau or GFAP during the first 24 hours after trauma do not seem to be able to predict PPCS. Future research testing of other biomarkers is needed in order to determine their usefulness in predicting PPCS when combined with relevant clinical data.